2017
DOI: 10.2109/jcersj2.16263
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of lead-free perovskite (Bi<sub>1/2</sub>K<sub>1/2</sub>)(Zr<i><sub>x</sub></i>Ti<sub>1&minus;</sub><i><sub>x</sub></i>)O<sub>3</sub> powders

Abstract: We developed a hydrothermal synthesis method for lead-free perovskite (Bi 1/2 K 1/2 )(Zr x Ti 1¹x )O 3 (BKZT) powders. Singlephase BKZT powders with various nominal Zr contents as high as x = 0.10 were obtained using amorphous hydrous oxide (Zr x Ti 1¹x )O 2· nH 2 O precursors prepared by the hydrolysis of Zr-and Ti-alkoxides, whereas a reaction using a mixture of crystalline TiO 2 and ZrO 2 powders did not provide single-phase BKZT. Elemental analysis revealed that the Zr contents of the obtained BKZT powders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Bengagi et al 50) previously attempted to fabricate Zr-substituted BKT ceramics by the conventional solidstate reaction method and found that the products included two perovskite phases with different Zr/Ti ratios even after extended thermal annealing as long as 100 h. Thus, we attempted to synthesize (Bi 1/2 K 1/2 )Zr x Ti 1¹x O 3 (BKZT-x) powders by a modified hydrothermal technique. 51) As the first step, amorphous hydrous oxides (Zr x Ti 1¹x )O 2 •nH 2 O were prepared from alkoxides of Zr and Ti as precursors for the hydrothermal reaction. The hydrothermal reaction using the amorphous precursors successfully yielded single-phase BKZT-x powders with the nominal Zr contents as high as x = 0.10, whereas a mixture of BKT and ZrO 2 was obtained when TiO 2 and ZrO 2 were used as the starting materials.…”
Section: Compositional Modificationsmentioning
confidence: 99%
“…Bengagi et al 50) previously attempted to fabricate Zr-substituted BKT ceramics by the conventional solidstate reaction method and found that the products included two perovskite phases with different Zr/Ti ratios even after extended thermal annealing as long as 100 h. Thus, we attempted to synthesize (Bi 1/2 K 1/2 )Zr x Ti 1¹x O 3 (BKZT-x) powders by a modified hydrothermal technique. 51) As the first step, amorphous hydrous oxides (Zr x Ti 1¹x )O 2 •nH 2 O were prepared from alkoxides of Zr and Ti as precursors for the hydrothermal reaction. The hydrothermal reaction using the amorphous precursors successfully yielded single-phase BKZT-x powders with the nominal Zr contents as high as x = 0.10, whereas a mixture of BKT and ZrO 2 was obtained when TiO 2 and ZrO 2 were used as the starting materials.…”
Section: Compositional Modificationsmentioning
confidence: 99%
“…Within the titanate perovskite family, gradient core-shell structured nanoparticles of BaTiO3-Ba1-xSrxTiO3 have been prepared using BaTiO3 seed particles that were first acid-treated to leach Ba from the surface before being hydrothermally treated in aqueous Sr(OH)2•8H2O at 200 C. [255] Other substituted titanate perovskites whose hydrothermal synthesis has proved possible include, (Bi0.5K0.5)(ZrxTi1-x)O3 with x  0.1, [256] and Fe 3+ -containing SrFexTi1-xO3-δ with x  0.1 that showed photocatalytic activity for NO oxidation. [257] Co-doping of Bi and Co into strontium titanate gave materials with photocatalytic properties under visible light irradiation, [258] and La/Cr co-doping of hollow CaTiO3 cubes allowed for efficient photocatalytic hydrogen production.…”
Section: Substitutional Chemistry and Solid-solutions Of Perovskitesmentioning
confidence: 99%